2020
DOI: 10.47130/bitlissos.826779
|View full text |Cite
|
Sign up to set email alerts
|

The Reasonsfor Not Preferring Family Medicine Practice: The Case of Şanlıurfa Province

Abstract: Bu makalede bilimsel araştırma ve yayın etiği ilkelerine uyulmuştur. / In this article, the principles of scientific research and publication ethics were followed. Bu makalede kullanılan verilerin elde edildiği çalışma; Bitlis Eren Üniversitesi Etik İlkeleri ve Etik Kurulunun 06.10.2020 tarih ve e 2020/08-II numaralı kararıyla onaylanmıştır. / Bitlis Eren University, Ethical Principles and Ethics Committee has evaluated the method used for this study in terms of ethics and approved it with its decision numbere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this study, the effective examination scores of the bluecollar and unemployed workers were found to be higher than the white-collar group. In the literature, there are studies that found a relationship between the occupational group and patient satisfaction [12,13], and there are also those that could not find a relationship [10,11,14]. This can be explained by the high rate of occupational similarity in the patients participating in this study.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the effective examination scores of the bluecollar and unemployed workers were found to be higher than the white-collar group. In the literature, there are studies that found a relationship between the occupational group and patient satisfaction [12,13], and there are also those that could not find a relationship [10,11,14]. This can be explained by the high rate of occupational similarity in the patients participating in this study.…”
Section: Discussionmentioning
confidence: 90%
“…The responses to the statement "Because it is easy to reach the relevant branch specialist physician" were found to be highly positive in the participants' hospital preference. In a study conducted in Şanlıurfa, it was found that the fact that the system did not direct individuals to family practice was effective in individuals who did not prefer family practice (20). If family physicians with a reasonable number of registered patients can schedule appointments, unnecessary applications to secondary and tertiary health care services can be avoided through the referral chain, and cost-effective operations can be ensured.…”
Section: Discussionmentioning
confidence: 99%